Desnutrición como causa de trastornos hematológicos en prescolares y escolares - Erik Andres, Pazmiño Brito (2021)
ABSTRACT Child malnutrition is a global problem that affects a large number of children especially from low-income populations. It is considered a systemic disease which can trigger multiple alterations within the body, where hematological diseases are the most common. The objective of this research project was to evaluate malnutrition as a cause of hematological disorders in preschoolers and schoolchildren. The present study was conducted at a descriptive level with documentary design, non-experimental and with a cross-sectional cohort. The population studied were 61 bibliographic sources of which after applying the inclusion and exclusion criteria, 51 were selected for the development of this work. The bibliographies were collected from different databases and search engines such as Scielo, Scopus, LILACS, Dialnet, Science Direct, Redalyc, Google Scholar, University Repositories and WHO. After carrying out this study, it was concluded that malnutrition is directly associated with hematological alterations such as anemia, where the most common and important is the iron deficiency anemia, as well as parasitism was related as a trigger factor for malnutrition and anemia. This disease also affects several hematological parameters like hemoglobin, hematocrit and erythrocytes, altering them with respect to their reference values in children. There are several factors capable of causing the development of this condition where the most common and important are cultural, economic, biological, institutional, socio-environmental and demographic factors. Keywords: Malnutrition, hematological disorders, anemia, iron. Firmado electrónicamente por: DIANA CAROLINA CHAVEZ GUZMAN Reviewed by: Lcda. Diana Chávez ENGLISH PROFESSOR C.C. 065003795-5